Polymorphic self-assembly of pyrazine-based tectons at the solution–solid interface - Jana, Achintya; Mishra, Puneet; Das, Neeladri (Beilstein Journal of Nanotechnology, 2019)
Exploring the surface self-assembly of small molecules that act as building blocks (tectons) for complex supramolecular structures is crucial for realizing surface-supported functional molecular devices. Here, we report on the synthesis and surface self-assembly of a new pyrazine-derived molecule with pyridine pendants. Ambient scanning tunneling microscopy investigation at the solution–solid interface reveals polymorphic self-assembly of these molecules on a HOPG substrate. Two different molecular packing structures with equal distribution are observed. Detailed analysis of the STM images emphasizes the crucial role of weak intermolecular hydrogen bonding, and molecule–substrate interactions in the formation of the observed polymorphs. Such weak hydrogen bonding interactions are highly desirable for the formation of modular supramolecular architectures since they can provide sufficiently robust molecular structures and also facilitate error correction.
Keywords: highly oriented pyrolytic graphite (HOPG); organic molecules; pyrazine; pyridines; scanning tunneling microscopy; self-assembly